Identification of Illness Uncertainty in Veterinary Oncology: Implications for Service - Stoewen, Debbie L.; Coe, Jason B.; MacMartin, Clare; Stone, Elizabeth A.; Dewey, Catherine E. (Frontiers in Veterinary Science, 2019)
Uncertainty has been identified as the central psychological feature of illness experiences, necessitating a variety of coping strategies to effectively manage it and successfully adapt. The purpose of this qualitative study was to determine the expectations of veterinary clients accessing oncology care services at a tertiary referral center for dogs with life-limiting cancer. The study consisted of 43 dog owners participating in 30 independent in-person single and dyadic interviews conducted with standardized open- and closed-ended questions from April to October 2009. Thematic analysis (supplemented with content analysis) was performed on transcripts of the interview discussions. Uncertainty was inadvertently identified as a central theme of the clients' experience. The diagnosis of a serious, life-limiting cancer and its treatment appeared to move clients into a world of uncertainty, which affected their feelings, thoughts, behaviors, attitudes, and personal expectations in relation to their dog, and their expectations of the oncology service. With uncertainty appraised mostly as a danger, clients appeared to employ multiple coping strategies to reduce uncertainty in the effort to adapt to the new reality of living with and caring for a dog with cancer. The need to manage uncertainty influenced their expectations of the service, specifically for information, ongoing relationships, 24-h access, and timely care. Our findings have implications for the delivery of specialty oncology services and for client welfare. When working with owners of dogs with life-limiting cancer, results suggest health care providers can facilitate the management of uncertainty to enhance clients' psychological well-being, thereby supporting clients' successful adaptation to the cancer experience.